The FAD2 Gene in Plants: Occurrence, Regulation, and Role - Dar, Aejaz A.; Choudhury, Abhikshit R.; Kancharla, Pavan K.; Arumugam, Neelakantan (Frontiers in Plant Science, 2017)
Vegetable oils rich in oleic acid are more desirable than oils rich in polyunsaturated and saturated fatty acids. The biological switch of oleic acid to linoleic acid is facilitated by fatty acid desaturase 2 enzyme that is further classified into FAD2-1, FAD2-2, FAD2-3 and FAD2-4. The genes coding these enzymes have high sequence similarity, but differ mostly in their expression patterns. The seed-type FAD2 genes had evolved independently after segregation by duplication from constitutively expressed FAD2 genes. Temperature, light and wounding effectively regulate FAD2 expression in plants. FAD2 genes are expressed differently in different tissues of the plant, and the over-expression of FAD2 modifies physiological and vegetative characteristics. The activity of FAD2 leads to an increase in the content of dienoic fatty acids, and hence increases the resistance towards cold and salt stress. The thorough study of the FAD2 gene is important for understanding the expression, regulation and mechanism that will help in improving the quality of oil and stress resistance in plants.